2022
DOI: 10.1371/journal.pmed.1003930
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding syphilis test uptake using rapid dual self-testing for syphilis and HIV among men who have sex with men in China: A multiarm randomized controlled trial

Abstract: Background Low syphilis testing uptake is a major public health issue among men who have sex with men (MSM) in many low- and middle-income countries. Syphilis self-testing (SST) may complement and extend facility-based testing. We aimed to evaluate the effectiveness and costs of providing SST on increasing syphilis testing uptake among MSM in China. Methods and findings An open-label, parallel 3-arm randomized controlled trial (RCT) was conducted between January 7, 2020 and July 17, 2020. Men who were at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Fifth, our study recruited participant exclusively online with a relatively small sample size, this may limit the statistical inference and generalizations of the results. However, our empirical generalizability research found that the results were similar when the online survey was quantitatively generalized to a national, cross-sectional survey dataset on MSM in China [ 7 , 8 , 30 ]. And according to a previous study that when sample size is 10 times greater than the number of variables, the power of the result was enough [ 31 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Fifth, our study recruited participant exclusively online with a relatively small sample size, this may limit the statistical inference and generalizations of the results. However, our empirical generalizability research found that the results were similar when the online survey was quantitatively generalized to a national, cross-sectional survey dataset on MSM in China [ 7 , 8 , 30 ]. And according to a previous study that when sample size is 10 times greater than the number of variables, the power of the result was enough [ 31 ].…”
Section: Discussionmentioning
confidence: 78%
“…Syphilis self-testing provides a private and more convenient alternative to in clinic testing and results are provided quicker than blood test in clinics [ 5 , 6 ]. Syphilis self-testing is a process whereby a person can get kits from online testing programs and community-based organization programs, then collect a specimen from finger pricking, perform the test, and interpret the syphilis result themselves [ 7 , 8 ]. However, one unintended consequence is the syphilis self-testing coercion from others (including partners, healthcare providers, friends, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Previous economic evaluation on syphilis self-testing showed that syphilis self-testing is cheaper than facility-based testing (Wang et al, 2022 ). Our economic evaluation assessed the cost of different distribution approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that syphilis self-testing is acceptable among MSM in China with minimal harm (Cheng et al, 2020 ; Wang et al, 2020a , 2020b ). Two studies showed that syphilis self-testing could expand syphilis testing uptake among MSM in China (Wang et al, 2022 ) and Zimbabwe (Sri-Pathmanathan et al, 2022 ). Syphilis self-testing could decentralize testing and facilitate new service delivery models (Lu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid point-of-care tests are currently being developed and have the potential to increase testing, particularly in resource-limited areas, urgent care settings, and recently during the COVID-19 pandemic where decentralized self-testing was valuable. Early results for rapid tests are promising, and some tests may be combined to test for HIV as well [ 55 , 56 ].…”
Section: Diagnosismentioning
confidence: 99%